2015
DOI: 10.1007/s00520-015-2911-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of minimal enteral feeding on recovery in a methotrexate-induced gastrointestinal mucositis rat model

Abstract: PurposePatients suffering from gastrointestinal mucositis often receive parenteral nutrition as nutritional support. However, the absence of enteral nutrition might not be beneficial for the intestine. We aimed to determine the feasibility of minimal enteral feeding (MEF) administration in a methotrexate (MTX)-induced mucositis rat model and thereby determine the effect of MEF on recovery.MethodsMale Wistar rats were attached to swivel systems from day 1 to 5 after 45 mg/kg MTX IV injection. The MTX group cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
2
11
0
1
Order By: Relevance
“…This model has contributed greatly to the understanding of various apects of CIM (203). While (140), milk bioactives with/without other compounds (23,24,37,85,195), oral insulin (109), dexamethasone (115), and feeding strategies such as minimal enteral feeding (108).…”
Section: Models Of Cim In Rodents Strengths and Limitationsmentioning
confidence: 99%
“…This model has contributed greatly to the understanding of various apects of CIM (203). While (140), milk bioactives with/without other compounds (23,24,37,85,195), oral insulin (109), dexamethasone (115), and feeding strategies such as minimal enteral feeding (108).…”
Section: Models Of Cim In Rodents Strengths and Limitationsmentioning
confidence: 99%
“…4,5 Minimization of eating disruptions also is an important determinant of quality of life following transplant, at least in adolescents, 18 and maintenance of enteral intake may reduce mucositis severity. 6 Finally, improvement in complete CINV control may result in cost savings through reduction in PN use.…”
Section: Discussionmentioning
confidence: 99%
“…Through its effect on enteral intake, CINV in the HSCT population may also increase mucositis severity, increase the risk of hepatobiliary toxicity and increase gut acute GvHD (aGvHD) severity. [3][4][5][6] We have previously shown that complete chemotherapy-induced vomiting (CIV) control in pediatric HSCT patients is seldom achieved. 7 Nausea control in pediatric HSCT patients has never been evaluated using a validated tool.…”
Section: Introductionmentioning
confidence: 99%
“…Universidade Federal do Vale do São Francisco. (KUIKEN et al, 2016;KIM et al, 2015;REBER et al, 2015).…”
Section: Adriana Gradelaunclassified